2020
DOI: 10.1136/bmjopen-2019-035454
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and effectiveness of home-based therapy programmes for children with cerebral palsy: a systematic review

Abstract: ObjectiveTo assess the feasibility and effectiveness of home-based occupational therapy and physiotherapy programmes in children with cerebral palsy (CP), focusing on the upper extremity and reporting on child-related and/or parent-related outcomes.DesignSystematic review.Data sourcesElectronic searches were performed in MEDLINE, EMBASE, CINAHL, PsycINFO, OTseeker and PEDro, and in ICTRP and CENTRAL trial registers, from inception to 6 June 2019.Eligible criteriaThe review included all types of original studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
0
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(65 citation statements)
references
References 90 publications
1
40
0
8
Order By: Relevance
“…Home-based therapies for patients with CP seem to be feasible; however, the available studies have used diverse methods and strategies, and, therefore, it is hard to determine the impact of these kinds of therapies. 49 An efficient way to deliver these home-based therapies is using TR, which appears to be an option to improve physical function in patients with disabilities. However, most research has included low-quality evidence studies that make it impossible to determine the effectiveness of TR.…”
Section: Discussionmentioning
confidence: 99%
“…Home-based therapies for patients with CP seem to be feasible; however, the available studies have used diverse methods and strategies, and, therefore, it is hard to determine the impact of these kinds of therapies. 49 An efficient way to deliver these home-based therapies is using TR, which appears to be an option to improve physical function in patients with disabilities. However, most research has included low-quality evidence studies that make it impossible to determine the effectiveness of TR.…”
Section: Discussionmentioning
confidence: 99%
“…In recent times, there has been an increasing shift towards greater participation of primary caregivers in therapy for their children [46,47]. Studies have reported improved child and caregiver outcomes through this approach.…”
Section: Discussionmentioning
confidence: 99%
“… 67 They consider the home to be a safe environment for the child to unwind, wanting to be there for their child and to provide stimulation, but without forcing the child to practice activities. 68 The intention of parents to avoid emphasising the disability at home, in order to normalise the child’s condition, could be mentioned as a reason to decline home-based training. Parents may need guidance in stimulating and guiding their child in a playful way at home.…”
Section: Discussionmentioning
confidence: 99%
“…Parents may need guidance in stimulating and guiding their child in a playful way at home. 68 , 69 In addition, the interventions should include motivation sessions for children and parents. Alternating therapy periods at the centre and at home might be performed in parents’ situations in which their involvement is not possible.…”
Section: Discussionmentioning
confidence: 99%